LINC00634 is a novel prognostic biomarker for colon cancer associated with immune infiltration - Haiyan Wang; Yanyan Huang; Lina Zhou; Xiaotong Zhu; Xuan Ye; Yi Cen (BMC Gastroenterology)
Abstract Background Colon cancer is a highly heterogeneous and most common malignant tumor of the gastrointestinal tract, which is prone to metastasis in advanced stages, leading to a poor prognosis for patients. Methods To gain a comprehensive understanding of genes associated with the prognosis of colon cancer, we identified a gene set (DPP7, TRPM5, ASB6, LINC00634 and GABRD) with potential prognostic value via genome-wide overall survival (OS) analysis. Further, LINC00634 was silenced by constructing small interfering RNAs (siRNAs) in Colo-320 cells. Results Multifactorial Cox regression analysis revealed that LINC00634, TRPM5, age, T and M stages were independent risk factors for the prognosis of colon cancer patients. Nomogram demonstrated that these risk factors had favorable predictive ability for 1-, 3- and 5-year OS in colon cancer patients. In addition, high expression of LINC00634 had a worse prognosis for colon cancer patients compared to TRPM5. In vitro experiments showed that silencing LINC00634 significantly inhibited cell proliferation and migration, and promoted cell apoptosis. Finally, immune infiltration analysis revealed that colon cancer patients with high expression of LINC00634 had lower infiltration levels of myeloid dendritic cells (mDCs) and CD8+ T cells in their tumor microenvironment (TME). Conclusion Our study found that LINC00634 can be used as a novel prognostic and immunological marker for colon cancer.